Economic performance of fiscal policy instruments on economic growth in Algeria - Asmae ZAOUI; Fatima BOUDAOUD (Dirassat Journal Economic Issue, 2020)
The aim of this research is to examine the effectiveness and limits of the instruments of fiscal policy on economic activity through a theoretical and another empirical framework on the Algerian economy.Research results demonstrate that fiscal policy in Algeria plays an important role in macroeconomic stabilization, by stemming any foreclosure effect in recent years, in a context of improving the allocation of resources, in particular for the benefit of activity and economic growth. As a result, recommendations have been suggested; the challenge is to structure budgetary measures so that they facilitate an efficient redeployment of resources towards activities offering longer-term economic and social benefits.